Ketentuan Kompilasi Hukum Islam tentang Kekuasaan Orang Tua Memaksa Kawin Anak Usia 21 Tahun - Muhammad Ihwan (Program Pascasarjana Universitas Ibrahimy, 2023)
The occurrence of a marriage based on the consent of the child is a marriage requirement by the compilation of Islamic law article 16 paragraphs 1 and 2 that marriage is based on the consent of the prospective bride and groom, and the form of consent of the prospective bride can be in the form of a firm and real statement in writing, verbally, or with gestures and also by acting. silence as a sign of no objection to the marriage process. As explained in article 98 paragraph 1 of the compilation of Islamic law,